DESKRIPSI PERMASALAHAN UPAYA PENGEMBANGAN PARIWISATA BERKELANJUTAN DI DANAU TOBA SUMATERA UTARA (PROBLEM DESCRIPTION OF SUSTAINABLE TOURISM DEVELOPMENT EFFORT ON TOBA LAKE NORTH SUMATERA) - Porman Juanda Marpomari Mahulae (Inovasi, 2019)
This research is an attempt to find out the problems that faced in realizing a sustainable tourism management in the Lake Toba area. The measured indicators in this study are the basic indicators of the 5 main issues of sustainable tourism development that was developed by United Nation World Tourism Organization (UNWTO). This research is descriptive research with qualitative approach and reinforced with quantitative data. Based on the result of measurement of the basic indicators and the deepening done with the discussions conducted with the informants of the research, it is known that the actual settlement of the basic problem of sustainable tourism development in a tourist destination is still a big task for tourism stakeholders in the region. Based on the types of problems that exist, there is a need for development policies that related to: 1) improving the economy with tourism activities; 2) guarantee of regional welfare and local communities in the presence of tourism activities; 3) fulfillment of visitor satisfaction; 4) involvement of local communities in tourism management; and 5) guarantee of environmental sustainability. Keywords: development, sustainable tourism, Toba Lake